Infrared-permeable flame-retardant ABS composite material and preparation method and application thereof
By using the ratio control of MABS resin and PMMA resin in ABS materials, combined with the combination technology of low-molecular bromine flame retardant and liquid phosphate, the problem that existing flame retardant ABS materials cannot take into account infrared permeability, flame retardant and scratch resistance, achieving efficient flame retardant and scratch resistance.
Patent Information
- Application Number
- CN202411965382.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-30
AI Technical Summary
Existing flame retardant ABS materials cannot take into account infrared permeability, flame retardancy and scratch resistance, and are difficult to meet the requirements of intelligent control panel materials.
The MABS resin and PMMA resin are used as the matrix to control the ratio of the two, and combine the combination of low-molecular bromine flame retardant and liquid phosphate to improve the infrared permeability, scratch resistance and flame retardant effect of the material.
It achieves flame retardancy at V-2 or above under a lower flame retardant addition condition, while maintaining high infrared permeability and scratch resistance, and is suitable for intelligent control panel materials.
Smart Images

Figure BDA0005218217660000061 
Figure BDA0005218217660000071 
Figure BDA0005218217660000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ABS materials, and more specifically to an infrared-transmissive flame-retardant ABS composite material and a preparation method and application thereof. Background Art
[0002] With the rapid development of green and healthy smart homes, the performance requirements for smart control panel materials for smart home appliances, sanitary ware and other products are getting higher and higher. ABS resin is a ternary graft copolymer of acrylonitrile-butadiene-styrene, which has a balance of rigidity and toughness mechanical properties, excellent chemical resistance and dimensional stability, and is easy to process and shape. Among them, transparent ABS resin (MABS) also has good infrared transmittance and can be used for smart control panel materials. However, MABS itself has a low oxygen index and is flammable, and the surface hardness of its products is low, with a pencil hardness of only 2B~B, and poor scratch resistance, which fails to meet the requirements of smart control panel materials.
[0003] The MABS resin before modification is a highly transparent material, but after flame retardant modification, it usually becomes a non-transparent material, and the infrared transmittance performance is significantly reduced, making it difficult to take into account infrared transmittance, flame retardancy and scratch resistance at the same time. Patent CN103289294A proposes a transparent flame retardant ABS material, which introduces environmentally friendly bromine flame retardants, antimony flame retardant synergists, phosphorus flame retardant synergists and toughening agents into the transparent ABS resin matrix. After flame retardant modification, it can still maintain a high transparency and has good mechanical properties and weather resistance. However, it meets the flame retardancy of V-2 or above, and the transmittance can only reach 45-78%, and its scratch resistance also needs to be improved.
[0004] In addition, as an exterior part, the control panel has a high demand for weather resistance of the material, especially in some indoor and outdoor use scenarios with direct sunlight, the material's yellowing resistance has a great impact on its service life. At the same time, with the rapid development of green and healthy smart homes, there is an increasing demand for antibacterial and mildew-proofing in the use scenarios of some home appliances, sanitary ware and other products. How to make the material have weather resistance and antibacterial and mildew-proofing functions while ensuring infrared transmittance and scratch resistance is worth exploring and studying. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects and shortcomings of the existing flame-retardant ABS that cannot take into account infrared transmittance, flame retardancy and scratch resistance, and to provide an ABS composite material.
[0006] Another object of the present invention is to provide a method for preparing an ABS composite material.
[0007] Another object of the present invention is to provide an application of the ABS composite material in preparing a control panel material.
[0008] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0009] The present invention protects an ABS composite material, comprising the following components in parts by weight:
[0010] MABS resin 50-70 parts,
[0011] 20-30 parts of PMMA resin,
[0012] Flame retardant 10-15 parts,
[0013] The flame retardant comprises a low molecular weight bromine flame retardant and a liquid phosphate ester in a mass ratio of (4-15):1.
[0014] The ABS composite material of the present invention uses MABS resin and PMMA resin as matrices, and controls the ratio of the two to improve infrared transmittance and scratch resistance. A bromine-based flame retardant and a liquid phosphate ester are compounded to improve the flame retardant effect of the system, wherein the liquid phosphate ester can improve the flame retardant stability of the bromine-based flame retardant, increase the fluidity of the material, and make the material easier to drip and extinguish. Under the synergistic effect of the bromine-based flame retardant and the liquid phosphate ester, a flame retardancy of V-2 or above can be achieved under the condition of a lower amount of flame retardant added, thereby reducing the loss of infrared transmittance of the material due to the addition of the flame retardant.
[0015] It should be noted that the ratio of each component is particularly critical. Increasing the content of PMMA resin can improve infrared transmittance and scratch resistance, but affects impact strength and flame retardancy to a certain extent; and although too high a content of flame retardant is beneficial to improving heat resistance, it will affect infrared transmittance. The present invention optimizes the content of each component to achieve that the ABS composite material can simultaneously take into account infrared transmittance, flame retardancy and scratch resistance.
[0016] In addition, the low molecular weight flame retardant has good compatibility with the ABS system and stable physical and chemical properties. Compared with high molecular weight polymeric flame retardants, it can avoid precipitation in a long-term high temperature and high humidity environment, resulting in a decrease in the infrared transmittance and flame retardancy of the material.
[0017] The low molecular weight flame retardant in the present invention refers to a flame retardant with a relative molecular mass of less than 1200; preferably, the low molecular weight bromine-based flame retardant is selected from at least one of bromotriazine or tetrabromobisphenol A.
[0018] In some embodiments, the liquid phosphate is at least one of bisphenol A-bis(diphenyl phosphate) (BDP), triethyl phosphate (TEP) or tris(2,3-dichloropropyl) phosphate (TCPP); preferably bisphenol A-bis(diphenyl phosphate).
[0019] Preferably, the mass ratio of the low molecular weight brominated flame retardant to the liquid phosphate ester in the flame retardant is (5-14):1, more preferably (5-13):1.
[0020] In some embodiments, the MABS resin content that can achieve the purpose of the present invention can be 50 parts, 51 parts, 52 parts, 53 parts, 54 parts, 55 parts, 56 parts, 57 parts, 58 parts, 59 parts, 60 parts, 61 parts, 62 parts, 63 parts, 64 parts, 65 parts, 66 parts, 67 parts, 68 parts, 69 parts, and 70 parts.
[0021] In some embodiments, the PMMA resin content that can achieve the purpose of the present invention can be 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, and 30 parts.
[0022] In some embodiments, the flame retardant content that can achieve the purpose of the present invention can be 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, and 15 parts.
[0023] Conventional MABS resins and PMMA resins in the art can be used in the present invention.
[0024] Preferably, the MABS resin has a haze of 4% or less at a thickness of 2 mm (ASTM D1003), and a transparency of 85% or more at a thickness of 2 mm (ASTM D1003); more preferably, the haze is 0-2%, and the transparency is 88-92%.
[0025] Preferably, the PMMA resin has a haze of less than 1% at a thickness of 2 mm (ASTM D1003), and a transparency of more than 90% at a thickness of 2 mm (ASTM D1003); more preferably, the haze is 0-0.5%, and the transparency is 90-94%.
[0026] In some embodiments, the MABS resin has a melt flow rate (ASTM D1238) of 6 to 23 g / 10 min at 220° C. and 10 kg.
[0027] In some embodiments, the PMMA resin has a melt flow rate (ASTM D1238) of 8 to 17 g / 10 min at 230° C. and 3.8 kg.
[0028] The ABS composite material further comprises:
[0029] 0.3-0.7 parts of UV absorber, 0.3-0.7 parts of light stabilizer, 0.6-1.2 parts of transparent antibacterial and mildew-proof agent;
[0030] The transparent antibacterial and mildewproof agent is an oxazolinone compound and / or a chitosan compound.
[0031] The ABS composite material of the present invention adopts a compounding system of a bromine-based flame retardant and a liquid phosphate ester, which can achieve flame retardancy above V-2 level, and the amount of flame retardant added is relatively low, providing further room for improvement of the material. A specific amount of ultraviolet absorber and light stabilizer is added to improve weather resistance, so that it can be used in a long-term high temperature and high humidity environment; at the same time, a specific antibacterial and antifungal agent is added to provide antibacterial and antifungal properties, and will not significantly affect the infrared transmittance and scratch resistance of the material.
[0032] In some embodiments, the ultraviolet absorber is at least one of a benzotriazole compound, a triazine compound or a benzophenone compound; preferably a benzotriazole compound.
[0033] In some embodiments, the light stabilizer is a hindered amine compound and / or a hydroquinone compound, preferably a hindered amine compound.
[0034] In some embodiments, the invention further comprises 0.2-1 part of an antioxidant and 0.2-1 part of a processing aid.
[0035] Preferably, the antioxidant comprises a hindered amine primary antioxidant, or a combination of a hindered amine primary antioxidant and a phosphite secondary antioxidant.
[0036] The processing aids include but are not limited to lubricants, dispersants, white mineral oil, coupling agents, or a mixture of two or more thereof.
[0037] A method for preparing an ABS composite material comprises mixing raw material components in a formula amount uniformly, and performing melt blending and extrusion to obtain the ABS composite material.
[0038] The invention protects application of an ABS composite material in preparing a control panel.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] The invention provides an ABS composite material, which takes MABS resin and PMMA resin as a matrix, and controls the ratio of the two to improve infrared transmittance and scratch resistance; adopts a compound of a bromine flame retardant and a liquid phosphate ester to improve the flame retardant effect of the system, wherein the liquid phosphate ester can improve the flame retardant stability of the bromine flame retardant, increase the fluidity of the material, and make the material easier to drip and extinguish; under the synergistic effect of the bromine flame retardant and the liquid phosphate ester, the flame retardancy of V-2 or above can be achieved under the condition of a lower amount of flame retardant added, thereby reducing the loss of infrared transmittance of the material due to the addition of the flame retardant.
[0041] The ABS composite material of the present invention also has good weather resistance and antibacterial and mildew resistance, and can take into account the infrared transmittance, flame retardancy and scratch resistance of the material, and can be applied to control panel materials of household appliances, sanitary ware and other products. DETAILED DESCRIPTION
[0042] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.
[0043] The raw materials used in the following examples and comparative examples are as follows:
[0044] MABS resin:
[0045] MABS1#: MABS TR557, LG Chem; at 220°C and 10 kg, the melt flow rate (ASTM D1238) is 21 g / 10 min, the transparency (ASTM D1003) is 90%, and the haze (ASTM D1003) is 2%.
[0046] MABS2#: MABS TR551, LG Chem; at 220°C and 10 kg, the melt flow rate (ASTM D1238) is 8 g / 10 min, the transparency (ASTM D1003) is 90%, and the haze (ASTM D1003) is 1.9%.
[0047] PMMA resin:
[0048] PMMA1#: PMMA LG, Sumitomo Chemical Singapore Pte. Ltd.; at 230° C., 3.8 kg, the melt flow rate (ASTM D1238) is 10 g / 10 min, the transparency (ASTM D1003) is 92%, and the haze (ASTM D1003) is 0.5%.
[0049] PMMA 2#: PMMA LG2, Sumitomo Chemical Singapore Pte. Ltd.; at 230° C., 3.8 kg, the melt flow rate (ASTM D1238) is 15 g / 10 min, the transparency (ASTM D1003) is 92%, and the haze (ASTM D1003) is 0.5%.
[0050] Flame retardant:
[0051] Brominated flame retardant 1#: Brominated triazine, FR-245, Israel Chemical Company.
[0052] Brominated flame retardant 2#: Tetrabromobisphenol A, FR-1524, Israel Chemical Company.
[0053] Brominated flame retardant 3#: Brominated epoxy resin, F-3014, Israel Chemical Company.
[0054] Liquid phosphate ester: WSFR-BDP-N2, Zhejiang Wansheng Technology Co., Ltd.
[0055] Solid phosphate ester: WSFR-PX-220, Zhejiang Wansheng Technology Co., Ltd.
[0056] Nitrogen-based flame retardant: melamine cyanurate (MCA), Sichuan Fine Chemical Research and Design Institute.
[0057] Ultraviolet absorber 1#: Benzotriazole ultraviolet absorber, RIASORB UV-234, Rianlon Corporation.
[0058] Ultraviolet absorber 2#: triazine ultraviolet absorber, UV-1577, produced by BASF.
[0059] Light stabilizer 1#: Hindered amine light stabilizer, RIASORB UV-770DF, RIASON Corporation.
[0060] Light stabilizer 2#: hydroquinone light stabilizer, 2,5-di-tert-butylhydroquinone (DBH), Wuhan Kanos Technology Co., Ltd.
[0061] Antibacterial and mildew-proof agent 1#: organic transparent antibacterial and mildew-proof agent (oxazolinone), JDGKP-007DG, Jinda Nano Technology (Xiamen) Co., Ltd.
[0062] Antibacterial and mildew-proof agent 2#: Chitin-based organic transparent antibacterial and mildew-proof, KEPUYIN J160, Guangdong Kepuyin Biotechnology Co., Ltd.
[0063] Antibacterial and antifungal agent 3#: Silver-loaded glass antibacterial agent, IONPURE PZA, Ishizuka Glass Co., Ltd.
[0064] Antioxidants: RIANOX 1010 and RIANOX 168 in a mass ratio of 1:2, from Rianlon Corporation.
[0065] Processing aid: EBS B50, PT.CMS CHEMICAL INDONESIA.
[0066] The ABS composite materials in the following examples and comparative examples include the following steps:
[0067] The raw materials are mixed evenly, melt-blended, extruded and granulated to obtain the ABS composite material.
[0068] The melt blending is carried out using a twin-screw extruder, the extrusion temperature is 180°C to 225°C, the rotation speed is 200rpm to 350rpm, and the feeding speed is 220kg / h to 400kg / h.
[0069] Examples 1 to 14
[0070] This embodiment provides a series of ABS composite materials, and the raw material components thereof are shown in Table 1.
[0071] Table 1 Raw material components of Examples 1 to 14 (parts by mass)
[0072]
[0073] Comparative Examples 1 to 10
[0074] This embodiment provides a series of ABS composite materials, and the raw material components thereof are shown in Table 2.
[0075] Table 2 Raw material components of comparative examples 1 to 10 (parts by mass)
[0076]
[0077] Performance Testing
[0078] The ABS composite materials of Examples 1-14 and Comparative Examples 1-10 were subjected to the following tests. The results are shown in Tables 3-4.
[0079] Infrared transmittance: ABS composite material was used to prepare a 70mm×40mm×3mm square injection molding sample.
[0080] Tested by TU-1810PC UV-Vis-IR spectrophotometer.
[0081] Transparency: Tested according to standard ASTM D1003.
[0082] Haze: Tested according to standard ASTM D1003.
[0083] Scratch resistance: The scratch resistance is evaluated by using a friction color fastness meter: the test sample is rubbed back and forth 500 times with gauze, and the depth of the scratch is observed under a Leica microscope at 200 times. The shallower the scratch, the better, and the deeper the scratch, the worst. The evaluation is graded as follows: Worst -, Poor -, Ordinary 0, Better +, Best ++.
[0084] Pencil hardness: Tested according to ASTM D3363; Method: Place a 70mm×40mm×3mm square injection molded sample on a fixed horizontal surface. The pencil is at a 45° angle to the coating (pointing in the opposite direction of the tester) and the pencil is pushed away from the tester to draw a 6.5mm long stroke. This process starts with the hardest pencil until the pencil does not scratch the sample surface. The corresponding pencil hardness is the sample pencil hardness.
[0085] Xenon lamp aging: According to standard ISO 4892-2 method A cycle 1: filter: daylight filter 102min illumination + 18min spray irradiance: 0.51W / (·nm)@340nm; blackboard temperature: 63℃; box temperature:
[0086] 44℃; Relative humidity: 50%.
[0087] Flame retardant performance: UL94 flame retardant test standard, test sample thickness is 1.5mm.
[0088] Antibacterial rate: Standard GB / T 31402-2015 surface antibacterial performance test, bacteria type: Staphylococcus aureus.
[0089] Table 3
[0090]
[0091] Table 4
[0092]
[0093]
[0094] The results show that the ABS composite material of the present invention has high infrared transmittance, good transparency, strong scratch resistance, high flame retardancy, and good weather resistance and antibacterial properties. Its infrared transmittance is above 82%, transparency is above 80%, haze is below 15%, scratch resistance is above + level, pencil hardness reaches HB, 500h xenon lamp aging ΔE≤2.0, flame retardancy reaches V-2 level, and antibacterial rate is above 95%.
[0095] Compared with Example 1, the PMMA content in the ABS composite material of Comparative Example 1 is too high, and its infrared transmittance and scratch resistance are improved, but its flame retardant performance is significantly reduced, resulting in the material failing to reach V-2 level.
[0096] Compared with Example 1, Comparative Example 2 uses a polymerized bromine flame retardant, and its infrared transmittance and transparency are significantly reduced, and the haze is also significantly increased. Comparative Example 3 uses solid phosphate ester instead of liquid phosphate ester, resulting in a slight decrease in infrared transmittance and transparency, and an increase in haze. When bromine flame retardants or liquid phosphate esters are used alone in Comparative Examples 4 and 5, a higher addition amount is required to meet the flame retardancy of V-2 level, at which time the infrared transmittance and transparency decrease, and the haze increases. The ratio between low molecular bromine flame retardants and liquid phosphate esters in the flame retardant of Comparative Example 6 is too large, and the flame retardant grade does not reach V-2 level at this time. An equal amount of nitrogen flame retardant is used in Comparative Example 7, which does not reach the flame retardancy of V-2 level, and the infrared transmittance and transparency are greatly reduced, and the haze increases.
[0097] Compared with Example 1, when the antibacterial and mildew-proofing agent of Comparative Example 8 uses a silver-loaded glass antibacterial agent, the haze of the material is significantly increased. When the content of the antibacterial and mildew-proofing agent in Comparative Example 9 is increased, its infrared transmittance and transparency are reduced.
[0098] Compared with Example 1, the ultraviolet absorber and the light stabilizer in Comparative Example 10 are too high. Although the xenon lamp aging resistance is improved, the transparency is reduced and the haze is increased.
[0099] The above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. An ABS composite material, characterized in that: The composition includes the following components in parts by weight: MABS resin 50-70 parts, 20-30 parts of PMMA resin, Flame retardant 10-15 parts, The flame retardant comprises a low molecular weight bromine flame retardant and a liquid phosphate ester in a mass ratio of (4-15):
1.
2. The ABS composite material according to claim 1, characterized in that: The brominated flame retardant is selected from at least one of brominated triazine and tetrabromobisphenol A.
3. The ABS composite material according to claim 1, characterized in that: The MABS resin has a melt flow rate of 6 to 23 g / 10 min at 220° C. and 10 kg.
4. The ABS composite material according to claim 1, characterized in that: The PMMA resin has a melt flow rate of 8 to 17 g / 10 min at 230° C. and 3.8 kg.
5. The ABS composite material according to claim 1, characterized in that: The MABS resin has a transparency of 85% or more and a haze of 4% or less at a thickness of 2 mm.
6. The ABS composite material according to any one of claims 1 to 5, characterized in that: Also includes: 0.3-0.7 parts of UV absorber, 0.3-0.7 parts of light stabilizer, 0.6-1.2 parts of transparent antibacterial and mildew-proof agent; The transparent antibacterial and mildewproof agent is an oxazolinone compound and / or a chitosan compound.
7. The ABS composite material according to claim 6, characterized in that: The ultraviolet absorber is at least one of benzotriazole compounds, triazine compounds or benzophenone compounds.
8. The ABS composite material according to claim 6, characterized in that: The light stabilizer is a hindered amine compound and / or a hydroquinone compound.
9. A method for preparing the ABS composite material according to any one of claims 1 to 8, characterized in that: The raw material components in the formula are mixed uniformly, melt-blended and extruded to obtain the ABS composite material.
10. Use of the ABS composite material according to any one of claims 1 to 8 in preparing a control panel.
Citation Information
Patent Citations
Transparent flame-retardant ABS material, and preparation method and application thereof
CN103289294A
High-hardness transparent flame-retardant ABS (acrylonitrile butadiene styrene) composite and preparation method thereof
CN104371264A
Transparent plastic with antibacterial and mouldproof capacity and preparing method thereof
CN106084609A
Halogen-free flame-retardant material and preparation method thereof
CN116285283A
Spraying-free ABS (Acrylonitrile Butadiene Styrene) material suitable for automobiles and production process thereof
CN117362909A